EFFECT OF PRECLINICAL SKILL LAB TRAINING ON CLINICAL SKILLS OF STUDENTS DURING CLINICAL YEARS - Imran, Madiha; Khan, Saadat Ali; Aftab, Tehreem (Pakistan Journal of Physiology, 2018)
Background: Integration of clinical and preclinical teaching results in improvement of clinical acumen and better understanding of basic medical sciences. Keeping this in view, it was aimed to determine the efficacy of clinical skill lab (CSL) training during preclinical years on acquirement of clinical skills by the medical students. Methods: It was a descriptive study carried out at Foundation University Medical College. Based on convenience sampling, 4th year students who had received CSL training were compared with the 5th year students who had not received CSL training. Evaluation proforma was used. Students graded their clinical skills between non-satisfactory to excellent based upon recall. Results: Ninety-six students responded, 47 from 5th year and 49 from 4th year. Sixty-seven percent students of 4th year considered that CSL sessions benefitted them in ward learning. Seventy-three percent students rated their history-taking and general physical examination skills as very good. Eighteen percent of 5th year students graded them as good. For systemic examination and basic life support (BLS), 66% of 4th year and 82% of 5th year graded them satisfactory. Overall ward performance was rated very good by 60% of 4th year and 36% of 5th year students. However, 33% of 4th year and none from 5th year students rated it excellent. Improvement in communication skills was observed by 53% of 4th year and 45% of 5th year students; and 53% from 4th year and 36% from 5th year felt improvement in their confidence level. Conclusions: CSL sessions during preclinical years greatly benefit the students in clinical years to improve overall performance, communication skills, and confidence. Pak J Physiol 2016;12(3):30–2